PRODUKTIVITAS DAN BIAYA ALAT SISTEM KABEL LAYANG P3HH24 UNTUK PENGELUARAN KAYU - Dulsalam (Jurnal Penelitian Hasil Hutan, 2012)
A study on productivity and cost of logs extraction using P3HH24 skyline system tool was carried out in community forest of Sukaraja Village, Warungkiara Sub Regency, Sukabumi Regency in 2009. The objective is to find out information of productivity and cost of P3HH24 skyline system tool for logs extraction. Data on log volume and working time of logs extraction as well as transportation cost were collected. The study revealed that 1. Leg exctraction productivity ranged from 5.737 to 8.331 m² / rit with an average of 7.067 m²/rit. 2. Average cast of log extraction was Rp 9,244,-/m² lower than the previous cost (Rp 15,713,-/m²). The increasing efficiency of the average extraction cost was 34% 3. Log extraction using PJHH24 skyline system tool is feasible based on pay back period (1.3 years), net present value (Rp 154,734,164,-), IRR (76.73%) and B/Cratio (1.62). 4. Average land excposure caused by leg extraction using P3HH24 skyline system tool war 4% 5. Chain supporter and the endless cable drum need improvements to increase the efficiency of logs rcctraction using P3HH24 skyline system tool, motoric chain supporting and endless cable drum need improving.